Study of The Form, Meaning and Function of The Ngayikah Tradition in The Pasemah Tribe Community in Desa Rigangan I, Kec. Kelam Tengah, Kabupaten Kaur - Fera Rindiani; Fera Zasrianita; Wenny Aulia Sari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
The aim of this research is to examine the form, meaning, and function of the ngayikah tradition in the Pasemah tribe community in Rigangan I Village, Kec. Central Dark District. Kaur, this research uses qualitative research while the method used in this research is descriptive; the data source used is in the form, meaning, and function of the ngayikah tradition in the Pasemah tribal community in Rigangan I Village. The data obtained from this research is in the form of the meaning and the function of the ngayikah tradition in the Pasemah tribe community in Rigangan I Village. Data collection procedures include observation, interviews, note-taking, and documentation using data analysis in the form of data reduction, data presentation, and conclusions, or data verification, checking data validity, data triangulation, and source triangulation data on research stages. The results of this research concluded that this ngayikah tradition is still ongoing and preserved by the Pasemah tribe community in Rigangan I village, and this ngayikah tradition has several forms of functions and meanings that are not yet known to many people, including cotton, cloth, shawls, soap, chalk, rice. , money, candlenuts, turmeric, limes, flowers, betel leaves, bay leaves, rice, and coconut shoots. The function and meaning of the equipment used in this tradition have positive value and have positive expectations in it; therefore, every use of this equipment is interrelated and must be present and used in every tradition because it has been handed down from generation to generation by their ancestors in ancient times.